Antibiofilm Activity of an Exopolysaccharide from Marine Bacterium Vibrio sp. QY101 - Jiang, Peng; Li, Jingbao; Han, Feng; Duan, Gaofei; Lu, Xinzhi; Gu, Yuchao; Yu, Wengong (PLOS ONE, 2011)
Bacterial exopolysaccharides have always been suggested to play crucial roles in the bacterial initial adhesion and the development of complex architecture in the later stages of bacterial biofilm formation. However, Escherichia coli group II capsular polysaccharide was characterized to exert broad-spectrum biofilm inhibition activity. In this study, we firstly reported that a bacterial exopolysaccharide (A101) not only inhibits biofilm formation of many bacteria but also disrupts established biofilm of some strains. A101 with an average molecular weight of up to 546 KDa, was isolated and purified from the culture supernatant of the marine bacterium Vibrio sp. QY101 by ethanol precipitation, iron-exchange chromatography and gel filtration chromatography. High performance liquid chromatography traces of the hydrolyzed polysaccharides showed that A101 is primarily consisted of galacturonic acid, glucuronic acid, rhamnose and glucosamine. A101 was demonstrated to inhibit biofilm formation by a wide range of Gram-negative and Gram-positive bacteria without antibacterial activity. Furthermore, A101 displayed a significant disruption on the established biofilm produced by Pseudomonas aeruginosa, but not by Staphylococcus aureus. Importantly, A101 increased the aminoglycosides antibiotics' capability of killing P. aeruginosa biofilm. Cell primary attachment to surfaces and intercellular aggregates assays suggested that A101 inhibited cell aggregates of both P. aeruginosa and S. aureus, while the cell-surface interactions inhibition only occurred in S. aureus, and the pre-formed cell aggregates dispersion induced by A101 only occurred in P. aeruginosa. Taken together, these data identify the antibiofilm activity of A101, which may make it potential in the design of new therapeutic strategies for bacterial biofilm-associated infections and limiting biofilm formation on medical indwelling devices. The found of A101 antibiofilm activity may also promote a new recognition about the functions of bacterial exopolysaccharides.